(3JgPjH GddZIs - (3CHh efUhQ eMeO Hf CMeO Hf GdGRgQj, Hf WdMI,J (B370 (3g` s ((3Ydi Hf eMeO Hf UObI GHf THjH GdNaGLi GdMfai s)
(3ChdgG (B:s
(3MQa GdSjf (B: (3CHh GH GdeVGYa S W (B: (3JZdH Yf GHf GdCYQGHi (B: (3GdGSW ef GdQLGd GdWhjd GdQLdjf hGdTWW GdXdeI hGdTWW GdLGFQhf s
(3BNQgG (B:s
(3hbGd CHh SYjO fMhg BNQ cJGH GdWGA hgh BNQ GdLRA GdYGTQ ef cJGH fgPjH GddZI hjJdhg ai Chd GdMGOi YTQ cJGH GdOGd s
(3GdfSNI HgG MhGTs
(3HgG GVWQGH ai JQJjH GdChQGbs
(3hYdjgG JUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs